Intestinal lymphangiectasia in a dog: Clinical, ultrasonographic, endoscopic, and strain elastographic aspects - Iago Martins Oliveira; Wanessa Patrícia Rodrigues da Silva; Mariana Moreira Lopes; Naida Cristina Borges (Open Veterinary Journal)
Background: Primary intestinal lymphangiectasia in dogs is a condition characterized by dilation of the lymphatic vessels in the intestine. It has serious consequences, such as protein loss. Early diagnosis and appropriate treatment are essential for the quality of life of affected animals.